High Rate of Initially Overlooked Kaplan Fiber Complex Injuries in Patients With Isolated Anterior Cruciate Ligament Injury. Issue 8 (July 2021) - Berthold, Daniel P.; Willinger, Lukas; LeVasseur, Matthew R.; Marrero, Daniel E.; Bell, Ryan; Muench, Lukas N.; Kane, Zenon; Imhoff, Andreas B.; Herbst, Elmar; Cote, Mark P.; Arciero, Robert A.; Edgar, Cory M.
Background: Injuries to the Kaplan fiber complex (KFC) are not routinely assessed for in the anterior cruciate ligament (ACL)-deficient knee during preoperative magnetic resonance imaging (MRI). As injuries to the KFC lead to anterolateral rotatory instability (ALRI) in the ACL-deficient knee, preoperative detection of these injuries on MRI scans may help surgeons to individualize treatment and improve outcomes, as well as to reduce failure rates. Purpose: To retrospectively determine the rate of initially overlooked KFC injuries on routine MRI in knees with isolated primary ACL deficiency. Study Design: Case series; Level of evidence, 4. Methods: Patients who underwent isolated ACL reconstruction between August 2013 and December 2019 were identified. No patient had had Kaplan fiber (KF) injury identified on the initial reading of the MRI scan or at the time of surgery. Preoperative knee MRI scans (minimum 1.5 T) were reviewed and injuries to the proximal and distal KFs were recorded by 3 independent reviewers. KF length and distance to nearby anatomic landmarks (the lateral joint line and the lateral femoral epicondyle) were measured. Additional radiological findings, including bleeding, lateral femoral notch sign, and bone marrow edema (BME), were identified to detect correlations with KFC injury. Results: The intact KFC could reliably be identified by all 3 reviewers (85.9% agreement; Kappa, 0.716). Also, 53% to 56% of the patients with initially diagnosed isolated ACL ruptures showed initially overlooked injuries to the KFC. Injuries to the distal KFs were more frequent (48.1%, 53.8%, and 43.3% by the first, second, and third reviewers, respectively) than injuries to the proximal KFs (35.6%, 47.1%, and 45.2% by the first, second, and third reviewers, respectively). Bleeding in the lateral supracondylar region was associated with KFC injuries ( P = .023). Additionally, there was a positive correlation between distal KF injuries and lateral tibial plateau BME ( P = .035), but no associations were found with the lateral femoral notch sign or other patterns of BME, including pivot-shift BME. Conclusion: KF integrity and injury can be reliably detected on routine knee MRI scans. Also, 53% to 56% of the patients presenting with initially diagnosed isolated ACL ruptures had concomitant injuries to the KFC. This is of clinical relevance, as ACL injuries diagnosed by current routine MRI examination protocols may come with a high number of occult or hidden KFC injuries. As injuries to the KFC contribute to persistent ALRI, which may influence ACL graft failure or reoperation rates, significant improvements in preoperative diagnostic imaging are required to determine the exact injury pattern and to assist in surgical decision making.